Bibliographia brasiliana: rare books about Brazil published from 1504 to 1900 and works by Brazilian authors of the Colonial period, de Rubens Borba de Moraes - Lemos, Antonio Agenor Briquet de (Revista de Biblioteconomia de Brasília, 1984)
MORAES, Rubens Borba de. Bibliographia brasiliana: rare books about Brazil published from 1504 to 1900 and works by Brazilian authors of the Colonial period. Revised and enlarged edition. Los Angeles: University of California; Rio de Janeiro: Kosmos, 1983. 2v. (UCLA Latin American Center Publications. Reference series, v. 10)